Exploring micro enterprises business performance through entrepreneurial orientation, knowledge sharing and innovation / Zarina Salleh, Rohana Ngah and Zanariah Zainal Abidin. - Salleh, Zarina; Ngah, Rohana; Zainal Abidin, Zanariah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Micro Enterprises form the majority of business establishments in Malaysia. They represent more than 90 percent of such establishments in the country. Interestingly, most studies have shown that entrepreneurial orientation (EO) is an important element of entrepreneurship for micro enterprises. Hence, in the era of robustness of technology and explosion of knowledge, the role of knowledge sharing and innovation should be incorporated in investigating the performance of micro enterprises. This paper aims to explore the business performance of selected micro enterprises in Malaysia. One hundred and six micro enterprises owners took part in the survey. Partial Least Square was used to analyze the data. The results show that while entrepreneurial orientation on its own has no direct impact on business performance, the practice of knowledge sharing and innovation practices does. Entrepreneurial orientation and knowledge sharing have shown a strong impact on innovation where innovation reflects the impact of all variables on business performance. The study has also shown that knowledge sharing and innovation are being practiced actively in micro enterprises, thus providing a good platform for future research.